2008
DOI: 10.1007/s10532-008-9193-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation and metabolic pathway of pyridine by a Paracoccus sp. strain BW001

Abstract: A bacterial strain using pyridine as sole carbon, nitrogen and energy source was isolated from the activated sludge of a coking wastewater treatment plant. By means of morphologic observation, physiological characteristics study and 16S rRNA gene sequence analysis, the strain was identified as the species of Paracoccus. The strain could degrade 2,614 mg l(-1) of pyridine completely within 49.5 h. Experiment designed to track the metabolic pathway showed that pyridine ring was cleaved between the C2 and N, then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 43 publications
1
25
2
Order By: Relevance
“…An increase of the initial pyridine concentration to 3000 mg L 脌1 resulted in the complete failure to degrade pyridine. Similar phenomena were also observed by other researchers in the pyridine biodegradation systems [42,43], which could be attributed to the high recalcitrance and high toxicity of pyridine. In addition, the pyridine concentration in raw industrial wastewater was generally in the range of 20-500 mg L 脌1 [34].…”
Section: Effect Of Initial Pyridine Concentrations On Pyridine Degradsupporting
confidence: 89%
“…An increase of the initial pyridine concentration to 3000 mg L 脌1 resulted in the complete failure to degrade pyridine. Similar phenomena were also observed by other researchers in the pyridine biodegradation systems [42,43], which could be attributed to the high recalcitrance and high toxicity of pyridine. In addition, the pyridine concentration in raw industrial wastewater was generally in the range of 20-500 mg L 脌1 [34].…”
Section: Effect Of Initial Pyridine Concentrations On Pyridine Degradsupporting
confidence: 89%
“…16S rRNA ampliWcation was described as in a previous study [3], and the sequence was analyzed by an ABI 3730xl DNA analyzer (Applied Biosystems, USA). The result was blasted with other published 16S rRNA sequences by using the BLAST program of the National Center for Biotechnology Information (NCBI) database.…”
Section: Identiwcation and Characterization Of The Isolatementioning
confidence: 99%
“…Recently, Bai et al (2008) reported the complete degradation of 2,614 mg l -1 of pyridine at 49.5 h by Paracoccus sp. strain BW001.…”
Section: Effect Of Picoline Phenol and Formaldehyde On Pyridine Degrmentioning
confidence: 99%